2021
DOI: 10.1186/s13041-021-00827-1
|View full text |Cite
|
Sign up to set email alerts
|

Cirbp-PSD95 axis protects against hypobaric hypoxia-induced aberrant morphology of hippocampal dendritic spines and cognitive deficits

Abstract: Hypobaric hypoxia (HH) is a typical characteristic of high altitude environment and causes a spectrum of pathophysiological effects, including headaches, gliovascular dysfunction and cognitive retardation. Here, we sought to understand the mechanisms underlying cognitive deficits under HH exposure. Our results showed that hypobaric hypoxia exposure impaired cognitive function and suppressed dendritic spine density accompanied with increased neck length in both basal and apical hippocampal CA1 region neurons in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As the structural basis of memory and learning functions, dendritic plasticity has been proved to play a vital role in hypoxia‐induced cognitive deficits. 21 First, Golgi Staining was used to identify the dendritic plasticity. Locations of the CA1 region in hippocampus and distributions of basal and apical spines in pyramidal neurons were shown in Figure 4A .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the structural basis of memory and learning functions, dendritic plasticity has been proved to play a vital role in hypoxia‐induced cognitive deficits. 21 First, Golgi Staining was used to identify the dendritic plasticity. Locations of the CA1 region in hippocampus and distributions of basal and apical spines in pyramidal neurons were shown in Figure 4A .…”
Section: Resultsmentioning
confidence: 99%
“…The control group was kept under the normal condition as described above, whereas the other three groups were exposed to a hypoxic condition equal to an altitude of 6000 m by raising in a hypoxia cubage (Fenglei Co. Ltd.) for 14 days continuously according to our former report. 21 Mice were treated with continuous DHEA injection for 2 weeks simultaneous with exposure to hypoxia. The animals were sacrificed for further analysis after 1 week of behavioral testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that both acute and chronic HH cause cognitive impairment with complex mechanisms, including impaired brain self-regulation, glial vascular defects, oxidative stress, and neuroinflammation, which eventually translate into cognitive deficits ( Wang M. et al, 2022 ). Zhou et al (2021) subjected 8-week-old C57BL/6 mice to simulated 6000 m altitude exposure for 14 days and observed cognitive function impairment, PSD95 downregulation, and dendritic density decline. Xu et al (2014) demonstrated the notable impairment of cognitive function in rats subjected to simulated altitude exposure of 3600 m. Experimental data from Ji et al (2021b) indicated that after 4 and 8 weeks of 4300 m altitude exposure, the hippocampus and cortical neurons of rats showed swelling of neuronal mitochondria and an increase in neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%